2013
DOI: 10.1007/s11999-012-2708-6
|View full text |Cite
|
Sign up to set email alerts
|

Does Femoral Rotation Influence Anteroposterior Alpha Angle, Lateral Center-edge Angle, and Medial Proximal Femoral Angle? A Pilot Study

Abstract: Background Femoral rotation on AP radiographs affects several parameters used to assess morphologic features of the proximal femur but its effect on femoroacetabular impingement parameters remains unknown. Question/purposes We therefore evaluated and characterized the potential effect of femoral rotation on (1) AP alpha angle, (2) lateral-center edge angle (LCEA), and (3) medial proximal femoral angle (MPFA) on AP hip radiographs. Methods We took seven AP hip radiographs at intervals of successive femoral rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
(60 reference statements)
0
5
2
1
Order By: Relevance
“…12,17,18,21 Plain radiographs are subject to varying degrees of rotation that may affect the accuracy of alpha angle measurements. 22 For the alpha angle to be considered a credible radiographic indicator, it must be reliable. The authors found that with varying degrees of femoral rotation the alpha angle ranged from 39--621.…”
Section: Discussionmentioning
confidence: 99%
“…12,17,18,21 Plain radiographs are subject to varying degrees of rotation that may affect the accuracy of alpha angle measurements. 22 For the alpha angle to be considered a credible radiographic indicator, it must be reliable. The authors found that with varying degrees of femoral rotation the alpha angle ranged from 39--621.…”
Section: Discussionmentioning
confidence: 99%
“…Por esse motivo, Clohisy et al 37 sugeriram que a distância entre o bordo superior da sínfise púbica e a extremidade do cóccix deve ser de 1 cm a 3 cm. Variações no grau de rotação do quadril também podem prejudicar a avaliação da morfologia do fêmur proximal, 42 enfatizando a importância de radiografias padronizadas.…”
Section: Radiografiaunclassified
“…Therefore, Clohisy et al 37 suggested that the distance between the upper edge of the pubic symphysis and the end of the coccyx should be between 1 cm and 3 cm. Variations in the degree of hip rotation may also impair the assessment of the morphology of the proximal femur, 42 emphasizing the importance of standardized radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…These measurements have been shown to have good inter-observer reliability with radiologists assessing plain films [ 17 ]; however, the reliability of using plain film radiographs was brought into question by Barton et al [ 23 ], who felt that measurements on plain films were not adequately validated to 3D MRI. A pilot study using a single cadaveric specimen, looked at X-ray images taken at seven different degrees of hip rotation and found that each additional degree of internal rotation produced a reciprocal reduction in the medial proximal femoral angle by 0.36° and the α angle by 0.18° [ 24 ]. This suggests that care should be exercised while designing protocols for obtaining radiographs in each department to ensure rotation of the hip is kept as constant as possible.…”
Section: What Are the Predictors For Progression To Oa In Fai?mentioning
confidence: 99%